2016
DOI: 10.1002/14651858.cd006047.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Household interventions for preventing domestic lead exposure in children

Abstract: Analysis 2.4. Comparison 2 Environmental interventions (dust control) compared to no intervention or another intervention not aimed to influence domestic lead exposure, Outcome 4 Blood lead level ≥ 10.0 µg/dL (dichotomous): ICC 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 76 publications
1
29
0
Order By: Relevance
“…Despite these advances, several sources of occupational and community exposure to lead persist. 38,178,179 Leadglazed pottery is a notable source of exposure in several countries. 169,180 Infants in the womb can be exposed to lead via transplacental transfer, and nursing infants can be exposed to lead in breastmilk.…”
Section: Trends In Lead Exposurementioning
confidence: 99%
“…Despite these advances, several sources of occupational and community exposure to lead persist. 38,178,179 Leadglazed pottery is a notable source of exposure in several countries. 169,180 Infants in the womb can be exposed to lead via transplacental transfer, and nursing infants can be exposed to lead in breastmilk.…”
Section: Trends In Lead Exposurementioning
confidence: 99%
“…12 The focus is shifting from the care of symptomatic children toward a primary prevention approach targeting high-risk communities, as the most reliable and cost-effective strategy to protect children from lead toxicity. 12,66 Table 5 presents some recommendations for families to insure that their home is hazard-free with respect to lead contamination. It is critical that the individuals conducting residential abatement, or the removal, enclosure, or encapsulation of lead-based paint or lead-contaminated dust or soil receive appropriate training, and pregnant women, infants and children are out of the home environment during remediation and renovations in order to minimize further exposure to lead.…”
Section: Prevention Of Exposurementioning
confidence: 99%
“…The lack of outreach to the Indigenous community has resulted in further criticism regarding the focus on individual behaviours, such as regularly cleaning hands and tables and growing lawns, while not addressing the underlying factors which make these changes unviable, such as poverty in some of Mount Isa's Indigenous community (ABC 2017a). A review of research on the effects of programs aimed at adjusting household behaviour found insufficient evidence that household educational interventions were effective at lowering children's BLLs (Nussbaumer-Streit et al 2016). In addition to these programs, Mount Isa Mines claims to have reduced its emissions significantly over the last decade in response to the health threat from lead exposure (ABC 2017b, NPI 2018), although concerns about the accuracy of this data (Cooper et al 2017) and the health risks from current airborne emissions (Taylor et al 2014) continue to be raised.…”
Section: Blood Lead Levels In Mount Isamentioning
confidence: 99%